Pengaruh Kompleksitas Tugas, Tekanan Anggaran Waktu, Pengalaman Audit dan Due Professional Care terhadap Kualitas Audit: (Studi Empiris Auditor yang Bekerja pada Kantor Akuntan Publik Wilayah Jakarta Barat Tahun 2025) - Andrean Putra Kurniawan; Desy Anggraeni (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study aims to determine the Influence of Task Complexity, Time Budget Pressure, Audit Experience, and Due Professional Care on Audit Quality in Auditors at Public Accounting Firms in the South Jakarta Region in 2025. The data sampling technique is through the distribution of questionnaires directly to respondents using the purposive sampling method. The population in this study is auditors who work in 7 Public Accounting Firms and obtained 47 auditors who are sampled in this study. This study uses multiple linear regression analysis techniques and uses the Statistical Package For The Social Science (SPSS) version 22 and Microsoft Excel 2019 program test tools. The results of this study prove that the variable of task complexity has a positive and significant effect on audit quality, while time budget pressure, audit experience, and Due Professional Care have no effect on audit quality.